DIGITAL TRANSFORMATION OF METHODOLOGY FOR TEACHING RUSSIAN AS A FOREIGN LANGUAGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines key areas of digital transformation in methods for teaching Russian as a foreign language (RFL). It analyzes changes in the organization of the educational process and the impact of digital platforms and artificial intelligence technologies on the development of language competence. Particular attention is paid to new didactic formats, interactive services, electronic educational resources, and adaptive learning opportunities. The advantages and limitations of digital tools are outlined, as well as prospects for their integration into modern RFL teaching methods.